Assessment of a reporting radiographer-led discharge system for minor injuries: a prospective audit over 2 years. Issue 4 (25th April 2012) - Henderson, Deborah; Gray, William K; Booth, Lisa
Abstract : Background and purpose: In the UK, there is a continuing effort within the National Health Service to reduce patient waiting times in emergency departments (EDs). This audit aimed to evaluate whether a reporting radiographer-led discharge system could reduce waiting times from x-ray to discharge with no detrimental effect on patient outcomes. Methods: A prospective audit over 2 years was conducted. Patients were considered for discharge by a reporting radiographer-led service if they were >5 years old, attended the hospital ED between 9:00 and 17:00, Monday to Friday, had an injury below the elbow in the upper limb or below the knee in the lower limb that required an x-ray, and were able to be discharged home without further medical intervention. Outcomes of interest were overall waiting times, accuracy of diagnosis and re-attendance at the ED within 28 days. Results: Between July 2006 and June 2008, 497 patients met the inclusion criteria and were discharged home by the radiographer-led service, and 2632 were discharged home using standard practices. Overall waiting times were >20 min quicker for the radiographer-led service at 100.9 min. The false negative rate was reduced from 2.09% to 0.2%, and re-attendance at the ED within 28 days for the same injury was reduced from 3.27% to only 0.4% for radiographer-led discharge. Conclusions: The service reduced waiting times and re-attendance rates while improving the accuracy of diagnosis. The efficacy of such services should be further studied in relation to more complex patient groups.